นโยบายการพัฒนาท้องถิ่นตามความคิดเห็นประชาชน ในเขตองค์การบริหารส่วนตำบลชุมแพ อำเภอชุมแพ จังหวัดขอนแก่น - คำโล่, สิทธิศุทธิ์ (วารสารศรีล้านช้างปริทรรศน์, 2017)
งานวิจัยนี้มีวัตถุประสงค์ดังนี้ 1) เพื่อศึกษานโยบายการพัฒนาท้องถิ่นตามความคิดเห็นประชาชนในเขตองค์การบริหารส่วนตำบลชุมแพ อำเภอชุมแพ จังหวัดขอนแก่น 2) เพื่อเปรียบเทียบนโยบายการพัฒนาท้องถิ่นตามความคิดเห็นประชาชนในเขตองค์การบริหารส่วนตำบลชุมแพ อำเภอชุมแพ จังหวัดขอนแก่น ที่มี เพศ อายุ ระดับการศึกษา และรายได้ต่างกัน     3) เพื่อศึกษาข้อเสนอแนะของประชาชนเกี่ยวกับนโยบายการพัฒนาท้องถิ่นในเขตองค์การบริหารส่วนตำบลชุมแพ อำเภอชุมแพ จังหวัดขอนแก่น เครื่องมือที่ใช้ในการวิจัยคือแบบสอบถามมาตราส่วนประมาณค่า (Rating Scale) ตามแบบลิเคิร์ต (Likert Scale) กลุ่มตัวอย่างที่ใช้ในการวิจัยครั้งนี้ประชาชนในเขตองค์การบริหารส่วนตำบลชุมแพ อำเภอชุมแพ จังหวัดขอนแก่น จำนวน 376 คน ซึ่งกำหนดขนาดของกลุ่มตัวอย่างโดยวิธีการใช้สูตรการคำนวณขนาดตัวอย่างด้วยวิธีของ Taro Yamane สถิติที่ใช้ในการวิเคราะห์ข้อมูล คือ ค่าความถี่ (Frequency) และหาค่าร้อยละ (Percentage) ค่าเฉลี่ย () และส่วนเบี่ยงแบนมาตรฐาน (S.D.) ทดสอบค่าที t-test และการทดสอบความแปรปรวนทางเดียว (One-way ANOVA หรือ F-test) หากพบว่ามีความแตกต่างกันอย่างมีนัยสำคัญทางสถิติจะทำการทดสอบความแตกต่างรายคู่ด้วยวิธีการ เชฟเฟ่ (Scheffe’s Method) ผลการวิจัยพบว่า 1) นโยบายการพัฒนาท้องถิ่นตามความคิดเห็นประชาชนในเขตองค์การบริหารส่วนตำบลชุมแพ อำเภอชุมแพ จังหวัดขอนแก่น โดยรวมทั้ง 4 ด้าน อยู่ในระดับมาก มีค่าเฉลี่ยอยู่ที่ 3.91 เมื่อพิจารณาในแต่ละด้าน ด้านโครงสร้างพื้นฐาน อยู่ในระดับมาก มีค่าเฉลี่ย 4.18 ด้านทรัพยากรธรรมชาติและสิ่งแวดล้อม อยู่ในระดับมาก มีค่าเฉลี่ย 3.92 ด้านเศรษฐกิจ อยู่ในระดับมาก มีค่าเฉลี่ย 3.77 และด้านสังคม อยู่ในระดับมาก มีค่าเฉลี่ย 3.75      2) ผลการเปรียบเทียบบุคลากรที่มี เพศ อายุ และรายได้ ต่างกัน นโยบายการพัฒนาท้องถิ่นตามความคิดเห็นประชาชนในเขตองค์การบริหารส่วนตำบลชุมแพ อำเภอชุมแพ จังหวัดขอนแก่น โดยภาพรวม ไม่แตกต่างกัน ส่วนบุคลากรที่มีระดับการศึกษา ต่างกัน นโยบายการพัฒนาท้องถิ่นตามความคิดเห็นประชาชนในเขตองค์การบริหารส่วนตำบลชุมแพ อำเภอชุมแพ จังหวัดขอนแก่น โดยภาพรวมแตกต่างกัน อย่างมีนัยสำคัญทางสถิติที่ระดับ 0.05                       3) ข้อเสนอแนะของประชาชนเกี่ยวกับนโยบายการพัฒนาท้องถิ่นที่มีผลต่อประชาชนในเขตองค์การบริหารส่วนตำบลชุมแพ อำเภอชุมแพ จังหวัดขอนแก่น สามารถแยกเป็นรายด้าน มีรายละเอียดดังนี้ (1) ด้านโครงสร้างพื้นฐาน มากที่สุดคือ ถนนที่ใช้ชำรุด เป็นหลุมเป็นบ่อ จำนวนมากควรปรับปรุงซ่อมแซมให้สัญจรไปมาได้สะดวก (2) ด้านเศรษฐกิจ มากที่สุดคือ ควรมีการส่งเสริมการฝึกอาชีพเสริมให้กับประชาชนอย่างจริงจัง (3) ด้านสังคม มากที่สุดคือ ควรจัดสถานที่ออกกำลังกายให้ครบทุกหมู่บ้าน (4) ด้านทรัพยากรธรรมชาติและสิ่งแวดล้อม มากที่สุดควรสนับสนุนงบประมาณให้มีการขุดลอก ทำความสะอาด รางระบายน้ำ ที่อุดตันทุกปี           This research had the objective as follows 1) Studies development locality policy according to opinion of people in organization border administrates Tumbol part abounds a raft, amphur abounds a raft, 2) Khornkaen provinces for compare with development locality policy according to opinion of people in organization border s administrate Tumbol part s abound a raft, amphur abounds a raft, Khornkaen province, That have, gender, age, education level and the income       3) Differently study the suggestion of people about development locality policy of organization border administrate of tombon Chumphae, Amphur Chumphae, Khornkaen Province, a tool that use in the research is scale questionnaire about the value , (Rating Scale) , as an example chip , (Likert Scale) , the sample that use in the research were 376 persons in organization border administrates of tombon Chumphae, Amphur Chumphae, Khornkaen Province, The statistics that use in data analysis has to analyse personal factor of person answer the questionnaire, by value frequency distribution, (Frequency) and seek percentage value, (Percentage), Mean, standard Deviation (S.D.), t-test, (One-way ANOVA, or F-test), if meet that, There is the difference important implily statistics way will do difference test lays a pair with the way, (Scheffe's Method .            The results were found as follows:                1) The development locality policy that affect people in organization border administrates tombon Chumphae, Amphur Chumphae, Khornkaen Province, generally both of 4 a side, stay in many levels, be valuable share that 3.91 when, consider in each a side, infrastructure side , stay in many levels, be valuable share 4.18 natural resources side and the environment, stay in many levels, be valuable share 3.92 economic, stay in many levels, be valuable share 3.77 and social, stay in many levels, be valuable share 3.75, 2) The personnel comparison that have, gender, age, and the income, differently  development locality policy that affect people in organization border administrates tombon Chumphae, Amphur Chumphae, Khornkaen Province, by the overall image, not different, personnel part that is high class the education, differently, development locality policy that affect people in organization border administrates tombon Chumphae, Amphur Chumphae, Khornkaen Province, by overall different image, implily important statistics way that 0.05 level,                    3) The suggestion of people s about development locality policy that s affect people s in organization border s administrate tombon Chumphae, Amphur Chumphae, Khornkaen Province, can separate lay a side, There is the detail as follows, (1) The infrastructure side, most be, the road where use decayed, be full of ruts and holes, a lot of should adjust repair travel back and forth get convenient, (2) The economic, most be, be supposed to training occupation push adds to give with people seriously, (3) The social, most be, should very the place exercises every fully a village, (4) The natural resources side and the environment, most should support the budget has the scoop copies, clean a gutter lets off the water, that blocked every year.